Pengembangan Media Pembelajaran Interaktif Berbasis Android Untuk Pembelajaran Ilmu Pengetahuan Alam Kelas VIII SMP - Jodi Hardika; M. Yakub Iskandar; Nofri Hendri; Ulfia Rahmi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Learning natural sciences in class requires the right media so that it is more impressive about the nature that is brought to class. Media that can integrate natural conditions can be brought into the classroom to make the learning process more real. One way is to use interactive multimedia, this media is used in the learning process so that students are able to learn the material in real life without having to go directly into nature. This research uses R&D (Research and Development) research with a 4-D model with a flow of definition, planning, development and deployment. The validity results were 4.88 or 97.7% from the first media expert in the "Very Valid" category, 4.33 or 86.6% from the second media expert in the "Very Valid" category. So it can be concluded that the Android-based interactive learning media product that was developed based on the scores given from the two validators was overall declared "Very Valid". The results of material validity tests on Android-based interactive learning media products that have been developed are overall declared "Very Valid" with an average of 4.81 or 95.5%. From the results of practical trials with students as trial subjects, it shows that from the practical aspect the media received an assessment of 4.67 or 96.1%. so that the media is categorized as "Very Practical" to apply.